EFFECTS OF PROCESSED CASTOR OIL BEAN (R ICINUS COMMUNIS L) MEAL AND SUPPLEMENTARY DL- METHIONINE ON NUTRIENT UTILIZATION BY BROILER CHICKS - A. O. Ani; A.U Okorie (Journal of Animal and Plant Sciences, 2013)
The effects of processed castor oil bean (Ricinus communis L) meal (CBM) and supplementary DL- methionine on nutrient retention, carcass and organ weights of broiler chicks were investigated for five weeks. Two hundred and sixteen 7-day old broiler chicks (Anak strain) were randomly divided into 12 treatment groups of 18 birds each in a 4 x 3 factorial arrangement involving four processed CBM levels (0,10,15 and 20%) and three DL – methionine levels (0, 0.25 and 0.5%). During week 5 of the experiment, the apparent retention of the proximate components and the organs weights of birds were evaluated. Results showed that chicks on treatments 10-12 had lower (P<0.05) retention of DM, nitrogen, EE and NFE and lower (P<0.05) body weight, liver, kidney, spleen, heart and empty gizzard weights than birds on other treatments. Result showed that 10% and15% processed CBM can be included in the diet of broiler chicks without and with DL-methionine supplementation, respectively to enhance nutrient retention and for normal organ development of broiler chicks.
Keywords: castor oil bean meal; DL-methionine; effects; nutrient utilization; organ weights; broiler chicks